Enrollment Issue, Power Energy Management Approach and Structure of Control of Renewable Energy Microgrid: A Review - Mohd Fauzi, Mohamad Yusof; Abu Zaharin, Ahmad (Penerbit Universiti Malaysia Pahang, 2019)
he integration and emerging of distributed generation into the grid especially renewable energy source has brought solution of the problem increasing demand of electricity. The utilization of renewable energy as a source generation can minimize the effect of green house and reduce the cost of operation. The RE microgrids are the great power solution due to the capability to control and coordinate different level between the loads and generators. The energy management control is the key of successions to provide the power reliability in the RE microgrid. The problem of the optimal energy management has become widely investigated in order to achieve the optimize architecture structure of microgrid. This paper presents a details description, problem issue of microgrid and brief explanation about power energy management control. Section 2 will explain on the architecture control structure of microgrid. List of control technique of energy management operation that was present and proposed in the literature is details in section 3. The progression project of microgrid in the world was reported and suggestion of area interest for future research activity was proposed in section 4.